A Portray of Teaching English for Young Learners in Manado City: The Teacher’s Media, Method, and Challenges - Indah Wardaty Saud; Moon Hidayati Otoluwa; Khoirotun Nisa Assifa (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This study aimed at describing the teaching of English to the kindergarten students in Manado City which contributed to the improvement of English Teaching and Learning quality for young learners. This study employed a descriptive qualitative research design with 14 teachers who taught English in 5 kindergartens as participants. The data was collected through interview to the participants and documentation of English learning materials and media. Then, the data was analyzed by applying three techniques; data reduction, data display, and data verification. The results revealed that the teachers who taught English designed the learning materials such as the alphabet, numbers, colors, animals, and days. In terms of teaching and learning media, seven teachers (50%) used the textbooks provided by the school. Two teachers (14%) used flashcards to help them convey the teaching material. Three teachers (22%) used pictures and two teachers (14%) used songs. The researchers found that 36% of the teachers used story telling method, 22% used singing, 21% made small groups, 14% conducted repetition, and only 7% applied the Role Play method. Moreover, findings on the challenges faced by the teachers in teaching English showed that the students’ difficulty in pronouncing English words, inadequate time to teach English, and the teacher’s non-English academic background became the factors influencing the teaching and learning process in Manado City Kindergartens.Keywords: Teaching English, Young Learners, Media, Method, Challenges